1994
DOI: 10.1044/1058-0360.0303.67
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Remediating Persistent Lateral Lisps in Children Using Electropalatography

Abstract: Electropalatography (EPG) was used to train two 8-year-old girls with persistent lateral lisps. Pretreatment evaluations showed that the two speakers differed in the manner in which they produced lisps. Subject 1, who produced errors for /s/ and /z/ sounds only, produced these errors with linguapalatal closure across the alveolar ridge and no contact at the region of the molars. She remediated quickly (17 treatment sessions) and could produce correct productions in conversation when monitored. Subject 2 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…In this study, however, we considered increased age as a positive feature. Dagenais et al (1994) along with Dent et al (1995) note that the absence of visual or cognitive deficits in potential EPG candidates is significant. These can adversely affect a child's ability to follow the programme and thus depress progress.…”
Section: Factors Predicting Successful Therapymentioning
confidence: 97%
“…In this study, however, we considered increased age as a positive feature. Dagenais et al (1994) along with Dent et al (1995) note that the absence of visual or cognitive deficits in potential EPG candidates is significant. These can adversely affect a child's ability to follow the programme and thus depress progress.…”
Section: Factors Predicting Successful Therapymentioning
confidence: 97%
“…The palate is then connected to a computer via a data acquisition box [14] and tongue movements against the sensors on the palate are displayed on-line via the computer screen. EPG is therefore unique in providing both the clinician and patient with information about the dynamic movements underlying speech production, resulting in an explicit level of diagnosis and treatment not available from perceptual methods [14,15]. The ability of EPG to monitor tongue-to-palate movement for diagnosing and treating dysarthria is of particular interest in the paediatric population post-TBI, given that lingual deficits have been suggested as the level of physiological impairments underlying articulatory issues in this patient group [3,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported using EPG with children who presented with speech sound disorders (Carter & Edwards, 2004;Dagenais, Critz-Crosby, & Adams, 1994;Dagenais, 1995;Gibbon, 1999). Nordberg, Berg, Carlsson, & Lohmander (2008) study reported on two participants diagnosed with dysarthria secondary to dyskinetic cerebral palsy.…”
mentioning
confidence: 99%
“…The findings of their study suggest that EPG technology is beneficial in training individuals how to produce sounds that are not currently in their phonetic inventory, as well as "kick start articulatory change" in a child with abnormal articulatory productions (Gibbon & Wood, 2003, p. 369). Several studies (Dagenais et al, 1994;Dent et al, 1995;Gibbon & Hardcastle, 1987;Gibbon, Hardcastle, & Moore, 1990;Hickey, 1992) have reported that EPG has aided in the improvement of specific speech sounds (e.g., improving articulation of /s/, /r/, and true palatal sounds) in children who arenot advancing with traditional speech therapy approaches (McAuliffe & Cornwell, 2008). Dagenais et al (1994) examined the effects of EPG on the remediation of a persistent lateral lisp in two eight-year old typically developing participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation